2022
DOI: 10.1002/adma.202109973
|View full text |Cite|
|
Sign up to set email alerts
|

In Situ Silver‐Based Electrochemical Oncolytic Bioreactor

Abstract: In this study, it is shown for the first time that a reduced graphene oxide (rGO) carrier has a 20‐fold higher catalysis rate than graphene oxide in Ag+ reduction. Based on this, a tumor microenvironment‐enabled in situ silver‐based electrochemical oncolytic bioreactor (SEOB) which switched Ag+ prodrugs into in situ therapeutic silver nanoparticles with and above 95% transition rate is constructed to inhibit the growths of various tumors. In this SEOB‐enabled intratumoral nanosynthetic medicine, intratumoral H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…(4) To elevate the treatment efficiency, combined or synergistic therapy is usually encouraged. [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] Inspired by this, nanozymes can be integrated with immunotherapy, chemotherapy, and other ROS-highlighted therapy to magnify the treatment efficiency. This direction will also arouse more interests, propelling clinical translation especially when imparting these functions into one platform and realizing the all-in-one strategy.…”
Section: Discussionmentioning
confidence: 99%
“…(4) To elevate the treatment efficiency, combined or synergistic therapy is usually encouraged. [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] Inspired by this, nanozymes can be integrated with immunotherapy, chemotherapy, and other ROS-highlighted therapy to magnify the treatment efficiency. This direction will also arouse more interests, propelling clinical translation especially when imparting these functions into one platform and realizing the all-in-one strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To shed light on this principle, ROS level was surveyed since many reports have reported that Ag-mediated ROS production is beneficial for bacterial inhibition. ,, Herein, BBoxiProbeDHE probe solution, a cell membrane penetrating probe, was used since it could be specifically oxidized by ROS to produce red fluorescent substances whose intensity is proportional to the ROS level. Thereby, ROS positive cells were stained red in the whole nuclear region, and the red fluorescence in the nuclear region could be recorded by a fluorescence microscope.…”
Section: Antibacterial and Inflammation Mitigation Using Such Composi...mentioning
confidence: 99%
“…27−34 Typically, Ag-based nanoparticles have been documented to produce ROS to inhibit bacteria expansion and repress tumor. 35,36 Regarding this, the in situ introduction of Ag in Ag-βZ is expected to not only kill bacteria and mitigate bacteria-arised infection but also promote proliferations of human umbilical vein endothelial cells (HUVECs) for accelerating wound healing (Figure 1). Intriguingly, a spraying method was employed to augment the applicability because it features easy-to-operate convenience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis is an emerging programmed cell death with the characteristics of cell membrane rupture, continuous cell swelling, and leakage of intracellular proinflammatory mediators. During the pyroptosis process, the formation of inflammasomes activates the caspase 1 and pro-inflammatory cytokines (IL-1β and IL-18), and caspase-1 can cleave gasdermin D to release the N-terminal domain (GSDMD-N) which executes pyroptosis via its pore-forming activity. , To date, pyroptosis has attracted widespread concern in cancer therapy, and a variety of nanomaterials have been developed to elicit pyroptosis by photodynamic therapy, chemodynamic therapy, and so on. However, pyroptosis still inevitably suffers from setbacks arising from the intrinsic adaptive survival mechanism and treatment resistance of cancer cells. ,,,, Notably, recent studies have reported that autophagy may act as a checkpoint to negatively regulate pyroptosis, thus resulting in therapeutic resistance. …”
Section: Introductionmentioning
confidence: 99%